Immunological effects in patients with steroid‐refractory graft‐versus‐host disease following treatment with basiliximab, a CD25 monoclonal antibody. (16th November 2015) - Chakupurakal, Geothy; García‐Márquez, María Alejandra; Shimabukuro‐Vornhagen, Alexander; Theurich, Sebastian; Holtick, Udo; Hallek, Michael; Scheid, Christof; von Bergwelt‐Baildon, Michael
Abstract: Steroid‐refractory graft‐versus‐host disease (GvHD) is a complication following an allogeneic stem cell transplantation with limited therapeutic options. Studies have shown a response in up to 80% of patients with this condition after treatment with the CD25 monoclonal antibody, basiliximab. Despite the good responses to treatment, around 50% of the patients experience recurrence of their GvHD symptoms 4–6 wk following cessation of therapy. The in vivo changes in the following treatment with this antibody have not been elucidated so far. We treated 14 patients with severe steroid‐refractory GvHD with basiliximab weekly for 4 wk and monitored the changes in the T‐, B‐, NK‐ and dendritic cell subsets over this time period. The overall response to treatment was 92% (13/14) with 50% (7/14) achieving a complete response. Fifty four percentage (7/13) of the patients who responded showed recurrence of their GvHD symptoms. Contrary to expectations, our observations showed a significant depletion of the regulatory T‐cell subset following treatment. Our findings suggest that the undesirable depletion of the regulatory T cells along with the CD25 + acute inflammatory cells might be responsible for the high incidence of GvHD recurrence in this cohort of patients.